ANALISIS LAPORAN KEUANGAN BUMD PANGANDARAN TERHADAP PROSES PEMBUATAN IKAN ASIN JAMBAL ROTI SAMPAI DENGAN PEMASARAN ( STUDI KASUS BUMD DAN NELAYAN DI KABUPATEN PANGANDARAN) - Linda Fitriyanti (Jurnal Manajemen FE-UB, 2019)
Jambal roti "is a term for salted manyung fish. The processing business of "jambal roti fish" inPangandaran has the potential to be developed. One aspect that needs to be studied in developingthe business is the Financial and Marketing Reports. This study aims to determine the level ofmarketing changes from year to year and the safety of raw materials and products, the level ofapplication of the Basic Feasibility Program, the correlation between the postrigor mortis anglewith the organol eptic value of raw materials, the double correlation between the organolepticvalue of raw materials and the level of application of the Basic Feasibility Program with theorganoleptic value of the product, the correlation between the education and business experienceof the processors with the level of implementation of the Basic Feasibility Program, as well asdetermining Critical Control Points (CCP) in the processing of "bread jambal fish" inPangandaran. This type of research is a case study, with the subject of research is the processingunit "fish jambal roti" totaling 9 units. All processing units are used as research samples, exceptfor testing the total bacterial content (Total Plate Count) only three sample processing units aretaken using a purposive sampling method. The results of the study showed that in general thequality of raw materials (average quality = 7, rounding) and product quality (average qualityvalue = 6.6) "bread jambal fish" in Pangandaran organoleptically had met the quality standardrequirements according to SNI. However, product safety is still in doubt because the average TPCis quite high (1.3 x 105 col oni / g) and exceeds the maximum standard of dried salted fish TPCaccording to SNI. Overall, the level of implementation of the Basic Feasibility Program is stilllow (average application rate = 54.78%). At a 5% confidence level, there is a real correlationbetween the post rigormortis angle and the value of organol eptic raw materials (r = 0.956).Likewise, the organoleptic value of raw materials and the level of application of the BasicFeasibility Program correlate significantly with the organol value of the product yield (R =0.978). Safer pengalelor correlated significantly with the level of application of the BasicFeasibility Program (r = 0.847). Meanwhile, between education and the level of implementationof the Basic Feasibility Program there was no real correlation (r = 0.020). The stage of theprocess that is stated as Critical ControlPoints (CCP) is the receipt of raw materials and drying.Keyword: Financial Statement Analysis, BUMD, Jambal Roti, Marketing, Pangandaran.